The Bank of England and the government debt : operations in the gilt-edged market, 1928-1972 - Allen, Bill, 1949- (Cambridge : Cambridge University Press, 2019)
The Bank of England and the Government Debt recounts the surprising history of the Bank of England's activities in the government securities market in the mid-twentieth century. The Bank's governor, Montagu Norman, had a decisive influence on government debt management policy until he retired in 1944, and established an auxiliary market in government securities outside the Stock Exchange during the Second World War. From the early 1950s, the Bank, concerned about inadequate market liquidity, became an increasingly active market-maker in government securities, rescuing the commercial market-makers in the Stock Exchange several times. The Bank's market-making activities often conflicted with its monetary policy objectives, and in 1971, it curtailed them substantially, while avoiding the damaging effects on liquidity in the government securities market that it had feared. Drawing heavily on archival research, William A. Allen sheds light on little-known aspects of central-banking and monetary policy.
Machine generated contents note: 1. Introduction; 2. Price and quantity discovery, market making and liquidity in the gilt market; 3. Government securities and the structure of the stock exchange; 4. Government debt management before 1928; 5. The gilt market and the Issue Department 1928-39; 6. Government debt management and the gilt market in the Second World War; 7. Post-War: 1945-51; 8. The gilt market from the reactivation of monetary policy until 1960; 9. Gilt market liquidity in the 1960s; 10. The high tide of intervention: 1960-66; 11. The conflict with monetary policy recognised and addressed: 1967-70; 12. Competition and credit control, 1970-72; 13. The Bank of England's contribution to market liquidity; 14. Governance in practice; 15. Conclusions; 16. Epilogue: bearing the cost of providing liquidity.
Title from publisher's bibliographic system (viewed on 04 Jan 2019).
Keywords: Bank of England -- History -- 20th century; Monetary policy -- Great Britain -- History -- 20th century; Banks and banking, Central -- Great Britain -- History -- 20th century; Debts, Public -- Great Britain -- History -- 20th century